329 GASTRECTOMY VERSUS ESOPHAGECTOMY FOR GASTROESOPHAGEAL-JUNCTION TUMORS: SHORT- AND LONG-TERM OUTCOMES FROM A NATIONAL AUDIT. (14th September 2020) - Jezerskyte, E; Mertens, A; van Dieren, S; Eshuis, W; van Berge Henegouwen, M; Gisbertz, S
Abstract:  : Both a total gastrectomy and an esophagectomy may be technically possible in a patient with a gastroesophageal (GEJ) carcinoma. The aim of this study was to investigate the morbidity, mortality, pathology results and long-term survival in patients following an esophagectomy or a total gastrectomy for GEJ cancer. Methods: A retrospective comparative cohort study of prospectively collected data from the Dutch Upper-GI Cancer Audit combined with survival data of the medical insurance database of the Netherlands was performed. Patients with a GEJ carcinoma in whom a total gastrectomy or an esophagectomy was performed, between 2011–2016 were included. Primary outcome was 3-year overall survival. Postoperative morbidity, mortality, 3-year conditional survival, reinterventions, radicality of surgery, (y)pTNM stage and lymph node yield were secondary endpoints. Results: A total of 999 patients were included: 918 underwent an esophagectomy and 81 underwent a gastrectomy. Postoperative morbidity (54.9% vs 49.4%, p = 0.336), mortality (30-day; 2.3% vs 3.7%, p = 0.436; 90-day: 1.9% vs 2.5%, p = 0.662) and 3-year conditional survival (38.3% vs 30.3%, p = 0.553) did not differ significantly between groups. A longer ICU-stay (median 2 [IQR1–4] vs 1 days [IQR0–2], p < 0.001) and a lower lymph node yield (median 17 [IQR 12–23] vs 21 [IQR 16–31], p < 0.001) were seen following esophagectomy. The 3-year overall survival was 37.4% after esophagectomy and 28.4% after gastrectomy (HR 1.047, 95%CI 0.795–1.380, p = 0.742). Conclusion: Patients with GEJ tumors after an esophagectomy required longer ICU-stay and had comparable short-term morbidity and mortality when compared to a total gastrectomy. Long-term overall and conditional survival was not significantly different between groups. The two procedures are therefore largely comparable from an oncological viewpoint, and the choice for either procedure might also be based on other outcomes such as quality of life.